2018
DOI: 10.1016/j.bbamem.2018.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of siRNA encapsulated nanoliposomes suitable for siRNA delivery by simply discontinuous mixing

Abstract: Previously a scalable and extrusion-free method has been developed for efficient liposomal encapsulation of DNA by twice stepwise mixing of lipids in ethanol and DNA solution using T-shape mixing chamber. In this study, we prepared nanoliposomes encapsulating siRNA by simply discontinuous mixing of lipids in ethanol/ether/water mixture and acidic siRNA solution without use of special equipment. The simple mixing siRNA/liposomal particles (siRNA/SMLs) prepared using ethanol/ether/water (3:1:1) mixture showed 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…For example, the encapsulation of biopharmaceuticals in liposomes leads to a modification in their pharmacokinetics and pharmacodynamics, improving their therapeutic activity [11]. Mokhtarieh et al have reported that the encapsulation of siRNA in liposomes prevented it from the RNase degradation and elimination [15]. Another example is related with the Cu,Zn-Superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the encapsulation of biopharmaceuticals in liposomes leads to a modification in their pharmacokinetics and pharmacodynamics, improving their therapeutic activity [11]. Mokhtarieh et al have reported that the encapsulation of siRNA in liposomes prevented it from the RNase degradation and elimination [15]. Another example is related with the Cu,Zn-Superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulties of utilizing lipid‐based conveyance vectors in the clinical setup are their harmfulness and their nonspecific activation of inflammatory cytokines and interferon reactions. Lipid‐based delivery vectors can be classified into five types of molecules: Cationic lipoplexes and liposomes; PEGylated lipids; Neutral lipids; Lipids particles; and Lipid‐like molecules (Kaczmarek et al, ; Liu et al, ; Mokhtarieh, Lee, Kim, & Lee, ; Muddineti, Shah, Rompicharla, Ghosh, & Biswas, ).…”
Section: Drug Delivery Systems For Sirna In Pulmonary Diseasesmentioning
confidence: 99%
“…The lipid-based delivery system is generally used to deliver siRNA in vitro and in vivo. Ordinarily, cationic lipids or liposomes utilizes negatively charged siRNA through electrostatic forces and are known as (Kaczmarek et al, 2018;Liu et al, 2019;Mokhtarieh, Lee, Kim, & Lee, 2018;Muddineti, Shah, Rompicharla, Ghosh, & Biswas, 2018).…”
Section: Lipid-based Delivery Vectorsmentioning
confidence: 99%
“…There have been several studies reported that proteins 7 and nucleic acids 26 can be loaded in DNA nanocages by far. However, nucleic acids, like siRNA have to be delivered to the cytoplasm or nucleus to exert therapeutic effects 22 , 27 . In other words, lysosomal escape is one of the key processes for the intracellular disposal of nucleic acid drugs 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%